Implementation Of Image Security On Electronic Wedding Card Using Secure Image Protection Algorithm - Anwar Saleh Daulay; Ahmad Fauzi; Khusnul Khair (CV. AFDIFAL MAJU BERKAH, 2022)
The marriage book is an official document in the form of a quote from the marriage certificate which is legal evidence of the existence of a marriage. Marriage books are given to couples who are legally married and are administratively registered in the country. The only interested parties who can issue a marriage certificate are the Office of Religious Affairs or KUA. With the sophistication of technology, there has been a modification of the marriage book, namely the marriage card which is designed as big as an ATM card. With the digital marriage card, it can make it easier for the bride and groom to carry a marriage book when going anywhere. The use of a marriage card can cause other adverse effects, one of which is that the security used is not guaranteed and the fear of misuse of the identity data of the spouse of the marriage card owner. Inside this marriage card, there is a barcode that contains partner data such as NIK, wedding date and even self-identity that is vulnerable to misuse. So, security is needed that can protect against theft of data that is secured through barcodes, so image security on electronic marriage cards is arranged using a secure image protection algorithm. Image processing is a process of processing pixels in a digital image for a specific purpose. Image processing and computer vision are used as the human eye, with image capture input devices such as cameras and scanners being used as eyes and computer machines (with their computational programs) being used as brains. that processes information. The Secure Image Protection algorithm is one method that can be used in processing the security image of this marriage card, which consists of system input, namely the image to be encrypted or decrypted and the key is then carried out the encryption or decryption process and then produces an output image that has hidden information. So that in the end we get a system that can secure the data on the marriage card in the form of an image processing pixel permutation system that is able to maintain the privacy of the confidentiality of the image on the electronic marriage card.